Produksi Bahan Bakar Minyak (BBM) dari Sampah Botol Plastik Bekas Air Minum dengan Metode Pirolisis - Dhaniswara, Trisna Kumala; Dian Fahriani (2477 - 6165, 2021)
Garbage is the biggest contributor to environmental damage, especially plastic waste that is not processed properly. One of the problems in the community is the management of plastic waste, which until now has not been controlled. It is estimated that each person consumes 170 plastic bags each year and that around 500 billion to one trillion plastic bags are used worldwide. As well as more than 17 billion plastic bags distributed free of charge by supermarkets around the world for each year. In fact, if all the plastic bags on earth were opened, they could cover the entire surface of the earth up to 11 times. Plastic is a material that is very familiar in human life and has been considered a staple for household or domestic needs so that the presence of plastic waste is increasing. The purpose of this research is to convert plastic waste bottles used for drinking water into fuel oil using the pyrolysis method. The reactor used is pyrolysis with a temperature of 200 °C, 250 °C, 300 °C, 350 °C, and 400 °C for 30, 60, and 90 minutes. After the fuel is obtained, it is taken for analysis of its heating value, flash point, ash content, moisture content, and composition analysis. The results of this research will help the processing of plastic waste in addition to used plastic bottles.